Future Directions in Endometriosis Research and Therapeutics - Nothnick, Warren B.; Marsh, Courtney; Alali, Zahraa (Current Women's Health Reviews, 2018)
Background: Endometriosis is a disease common among women of reproductive age characterized by pain, anxiety and infertility. Defined as the growth of endometrial tissue in ectopic locations, endometriosis remains an enigmatic disease for which current treatments are less than ideal. Much of these shortcomings to current therapy stem from our incomplete understanding on the pathogenesis of the disease. It is generally accepted that endometriosis is an estrogen-dependent disease and, as such, the majority of treatment approaches aim at reducing estrogen action and/or production. Unfortunately, this approach is not effective in all women with endometriosis and in those women where success is achieved with their use, there is potential for health-comprising side effects. Objective: The objective of this review is to summarize current approaches for treatment of endometriosis, discuss their limitations and potential reasons for lack of progress towards better therapeutics for this disease. Results: In this review we summarize the current approaches for treatment of endometriosis, discuss their limitations and potential reasons for lack of progress towards better therapeutics for this disease. Conclusion: Based upon the current state of knowledge, there is a strong necessity for through assessment at the level of the genome, miRNAome and proteome as well as the importance of integrating clinically-relevant endpoints in future studies which evaluate potential endometriosis therapies in experimental models of endometriosis.
Keywords: estrogen-sparing